An industrial quality control study of Bayer CropScience Philippines, Inc. - Baguio, Rhea Monica N.; Cabrillos, Marianne C.; Ocampo, Jan Astrid R.
A Statistical Control Study was done for Bayer CropScience Philippines. Only the primary product would be considered for this study. Due to request for confidentiality, this product would be referred to as Product A. A Failure Modes and Effects Analysis was used to determine the possible problems that can be encountered and recommendations were developed. The levels of Active Ingredient content were obtained for Product A, and Moving Range Charts and Control Charts for Individual was constructed with the Specification Limits Dictated by law. It was determined that the samples were out of control in terms of the tests for trends and controllability, such as "6 points in a row, all increasing", "and were two out of three points more than two sigma from the centerline", and "four or five points beyond one sigma from the centerline". For the pesticide industry however, only outliers were deemed important to be considered in determining the level of control in the context of the active ingredient. In these terms therefore, the process is in control. Based on the control charts presented, assignable causes for the out of control points must be addressed, even though the second set of control charts illustrate that the process is in control to ensure homogeneity among batches. A new set of control charts were developed. These charts can be used for the present for incoming batches of products. The process capability is also analyzed. Since it shows from the process capability analysis that the process can still be improved, analysts should be hired. Such an investment would yield significant results in terms of meeting the plant's potential. A simple way of improvement is to standardize the measurements in order to reduce errors in the ratio of the materials. Sticker implementation of the proportions for the raw materials should be imposed.